Implementation Of Ramadan Fasting at MI Manbaul Islamic High School - Febrianti, Winda; Sukarsih, Winda; Setiawan, Wawan; Wardin; Yantika, Windi (Jurnal Cendekia Islam Indonesia, 2025)
This article discusses the implementation of Ramadan fasting in grade 3 students of MI Manbaul Islamiyah, which aims to instill spiritual values ​​and discipline through fasting. This study was conducted using observation and interview methods with teachers and students to determine the understanding and implementation of fasting among students. The results of the study indicate that Ramadan fasting not only functions as a religious obligation, but also as a means of character education, developing self-awareness, and strengthening social relations between students and the surrounding environment. In addition, this article also identifies the challenges faced by students in carrying out fasting, such as physical problems and study time management, as well as efforts made by the school to support the smooth implementation of this worship. The implementation of Ramadan fasting in grade 3 MI Manbaul Islamiyah has a positive impact on the development of students' character, especially in terms of mental resilience and Islamic values ​​applied in everyday life.